1996
DOI: 10.1016/0014-5793(96)00873-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominant role of mitochondria in protection against a delayed neuronal Ca2+ overload induced by endogenous excitatory amino acids following a glutamate pulse

Abstract: The objective of this study was to evaluate the contribution of mitochondria to the clearance of Ca 2+ loads induced by glutamate or 25 mM K ÷ pulses. The mitochondrial Ca 2+ uptake was suppressed by application of 0.5 ttM antimycin A or 3-5 mM NaCN in combination with 2.5 Ixg/ml oligomycin. In most cells such treatments both in the presence and in the absence of external Na + failed to abolish the early fast phase of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…However, it is at present unclear which processes may be participating in this Ca¥ transport. Several previous studies have documented the role of mitochondria in buffering depolarization-or glutamateinduced [Ca¥]é changes in neurones (Thayer & Miller, 1990;Werth & Thayer, 1994;White & Reynolds, 1995;Kiedrowski & Costa, 1995;Wang & Thayer, 1996;Khodorov et al 1996). However, these previous studies have not explicitly documented the role of mitochondria in kainateinduced [Ca¥]é changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is at present unclear which processes may be participating in this Ca¥ transport. Several previous studies have documented the role of mitochondria in buffering depolarization-or glutamateinduced [Ca¥]é changes in neurones (Thayer & Miller, 1990;Werth & Thayer, 1994;White & Reynolds, 1995;Kiedrowski & Costa, 1995;Wang & Thayer, 1996;Khodorov et al 1996). However, these previous studies have not explicitly documented the role of mitochondria in kainateinduced [Ca¥]é changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have focused on NMDA receptor-mediated Ca¥ loads have suggested that Ca¥ uptake by mitochondria is an important mechanism for buffering [Ca¥]é changes, and that mitochondria become progressively more important as the intensity of the stimulus increases (White & Reynolds, 1995, 1997Wang & Thayer, 1996;Khodorov, Pinelis, Storozhevykh, Vergun & Vinskaya, 1996). It has also become evident that mitochondrial Ca¥ loading shapes the recovery from increases in [Ca¥]é because the time necessary for [Ca¥]é to return to baseline following NMDA receptor activation is dominated by the Ca¥ release from the mitochondrial pool that is mediated by mitochondrial Na¤-Ca¥ exchange (Nicholls & Akerman, 1982;Kiedrowski & Costa, 1995;Wang & Thayer, 1996;White & Reynolds, 1997).…”
mentioning
confidence: 99%
“…Neuronal survival is intimately linked to mitochondrial homeostasis. Mitochondria supply the central nervous system with energy (ATP), as well as regulating calcium within the cell (Khodorov et al, 1996). Several therapeutic interventions that target stabilizing mitochondria have shown promising results by reducing overall neuronal tissue damage as well as enhancing neurological outcome following TBI (Verweij et al, 1997;Sullivan et al, 1999;Sullivan et al, 2004;Hino et al, 2005;Xiong et al, 2005;Clark et al, 2007).…”
mentioning
confidence: 99%
“…Thus, mitochondrial membrane potential can be regarded as a factor contributing to intracellular Ca 2+ reg ulation in neurons, which definitely occurs during activa tion of Glu receptors. Khodorov et al [26] showed that antimycin, an inhibitor of the 3rd complex of the electron transport chain, combined with the inhibitor of ATP syn thase, oligomycin, significantly inhibits Ca 2+ uptake into mitochondria. The latest data show that Ca 2+ uptake into mitochondria depends on the degree of their association with cytoskeleton.…”
Section: Toxic Action Of Glutamate Causes Accumulation Of Calcium In mentioning
confidence: 99%